DSA electrode, preparation method thereof and dye wastewater treatment method
By preparing TiO2-NTs intermediate layer and SnO2-Sb2O4-La composite material layer on the DSA electrode, forming Ti/TiO2-NTs/SnO2-Sb2O4-La electrode, the problems of decreasing activity and short service life of traditional electrodes are solved, and the problem of Efficient degradation and stability of dye wastewater are improved.
Patent Information
- Application Number
- CN202411484036.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional DSA electrodes have problems of decreased activity and short service life when treating dye wastewater, which limits their promotion in practical applications.
Titanium substrate is used as the base plate, and TiO2-NTs intermediate layer is prepared by anodizing method, and SnO2-Sb2O4-La composite material layer is deposited thereon to form Ti/TiO2-NTs/SnO2-Sb2O4-La electrodes, and the electrode is improved by calcining treatment. stability and electrocatalytic properties.
Without reducing the oxygen absorption potential, the electrocatalyticity and stability of the electrode are improved, the service life is extended, and the efficient degradation of pollutants in dye wastewater is achieved without secondary pollution.
Smart Images

Figure CN119191491A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of dye wastewater treatment, and in particular to a DSA electrode and a preparation method thereof, and a dye wastewater treatment method. Background Art
[0002] With the rapid development of industrialization and urbanization, organic dye pollution has become an increasingly serious environmental problem. In particular, organic dye wastewater has attracted much attention due to its high toxicity, difficulty in degradation and bioaccumulation.
[0003] In recent years, organic dyes have attracted widespread attention due to their persistent toxicity and light pollution. Currently, the annual production of dyes in the world is about (8-9)×10 5 As a major textile production and processing country, my country has been the world's largest textile exporter for many years, with an annual dye production of 1.5×10 5 t, of which about 10% to 15% of the dyes will be directly discharged into the water, causing serious damage to the ecological environment. Secondly, some dyes are carcinogenic and neurotoxic, posing a threat to the life safety of animals and humans.
[0004] Traditional methods for treating organic dyes, such as physical adsorption, chemical precipitation and biodegradation, often have problems such as low treatment efficiency, high cost and easy secondary pollution.
[0005] Common dye components in dye wastewater include rhodamine B (RhB), methylene blue (MB) and methyl orange (MO). In recent years, electrochemical technology has attracted widespread attention in the treatment of dye wastewater due to its advantages such as high efficiency and environmental protection. In electrochemical technology, the selection of electrode materials is crucial. Dimensionally stable anode (DSA) is a new type of insoluble anode material with excellent electrocatalytic performance and stability. However, traditional DSA electrodes have problems of decreased activity and short service life when treating wastewater, which limits their promotion in practical applications.
[0006] Therefore, there is a need to improve the electrodes in electrochemical technology to increase the service life of the electrodes, reduce processing costs, and reduce maintenance work. Summary of the invention
[0007] The object of the present invention is to provide a DSA electrode and a preparation method thereof, and a dye wastewater treatment method, so as to solve the technical problems in the prior art that the traditional DSA electrode has decreased activity and short service life when treating dye wastewater.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] In the first aspect, the present invention discloses a DSA electrode for purifying dye wastewater, comprising a titanium substrate, a TiO2-NTs intermediate layer attached to the titanium substrate, a SnO2-Sb2O4-La composite material layer attached to the side of the TiO2-NTs intermediate layer away from the titanium substrate, wherein the SnO2-Sb2O4-La composite material layer has a thickness of 0.2 to 0.8 mm.
[0010] The modification of the intermediate layer of the DSA electrode disclosed in the present invention with titanium dioxide nanotubes (TiO2-NTs) can improve the electrocatalytic property and stability of the electrode without reducing the oxygen absorption potential. The ordered three-dimensional structure of TiO2-NTs effectively increases the load of the SnO2-Sb2O4-La coating and enhances the stability of the electrode. At the same time, the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs. At the same time, the introduction of TiO2-NTs increases the load of the coating and improves the stability and pollutant degradation rate, thereby extending the service life of the electrode. The DSA electrode disclosed in the present invention can utilize the free radicals (such as hydroxyl free radicals, etc.) generated during the electrolysis process as oxidants to degrade pollutants when the electrochemical oxidation method is used to purify dye wastewater, and has the advantages of high efficiency and no secondary pollution.
[0011] Preferably, the dye wastewater is dye wastewater containing rhodamine B, or dye wastewater containing methylene blue, or dye wastewater containing methyl orange.
[0012] In a second aspect, the present invention further discloses a method for preparing a DSA electrode, using the DSA electrode as described above, comprising the following steps:
[0013] S1, pre-treating the titanium substrate;
[0014] S2, placing the pretreated titanium substrate into a reactor and using it as an anode to prepare a TiO2-NTs intermediate layer by an anodic oxidation method, wherein the TiO2-NTs intermediate layer is attached to the surface of the titanium substrate;
[0015] S3, using the titanium substrate with the TiO2-NTs intermediate layer attached thereto as a cathode, and depositing a SnO2-Sb2O4-La composite material deposition layer on the side of the TiO2-NTs intermediate layer away from the titanium substrate by an electrodeposition method;
[0016] S4. Calcine the titanium substrate with a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer, control the calcination temperature and time, and obtain a Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer, that is, the obtained DSA electrode.
[0017] This scheme adopts the method of first preparing an intermediate layer, then depositing, and then calcining to attach a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer on a titanium substrate. At the same time, during the deposition and calcination process, the ratio of each component, deposition time, calcination time and calcination temperature are controlled, so that the obtained DSA electrode can improve the electrocatalytic property and stability of the electrode without reducing the oxygen absorption potential when used to purify dye wastewater, and can have an efficient degradation rate and a high removal rate for the dye component.
[0018] Preferably, in step S2, preparing the TiO2-NTs intermediate layer includes the following steps: first, placing the pretreated titanium substrate in a mixed solution containing NH4F and ethylene glycol, using the titanium substrate as an anode and a graphite electrode as a cathode, oxidizing at a constant voltage to obtain amorphous TiO2-NTs, and then annealing at a constant temperature to obtain TiO2-NTs crystals, wherein the TiO2-NTs crystals are attached to the surface of the titanium substrate in a layered structure to obtain a titanium substrate with a TiO2-NTs intermediate layer attached.
[0019] Preferably, in step S3, depositing the SnO2-Sb2O4-La composite material layer comprises the following steps:
[0020] S3.1. Place a titanium substrate with a TiO2-NTs intermediate layer in a reactor and use it as a cathode. Use a graphite electrode as an anode. Connect the cathode and the anode to the negative and positive electrodes of a power source through electrical wires, respectively.
[0021] S3.2, preparing a mixed solution according to a preset mixing ratio, adjusting the pH of the mixed solution to acidic, and then adding the mixed solution to a reactor, wherein the raw materials used to prepare the mixed solution include SnCl4·5H2O, Sb2O3, and La(NO3)3·6H2O;
[0022] S3.3. Turn on the power supply to maintain a specific current density between the cathode and the anode, so that the substances in the mixed solution are deposited on the titanium substrate. After the preset deposition time, a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer is formed on the titanium substrate, and the deposition thickness is 0.2 to 0.8 mm.
[0023] Preferably, in step S2, the constant voltage is in the range of 20 to 30 V, the oxidation time is in the range of 150 to 200 min, the constant annealing temperature is above 400° C., and the annealing time is 1 to 2 h.
[0024] Preferably, in step S3, the mixed solution is prepared by sequentially adding SnCl4·5H2O, Sb2O3 and La(NO3)3·6H2O to an isopropanol solution, then sequentially adding hydrochloric acid and citric acid, and then first ultrasonicating and then stirring at a constant temperature to obtain a mixed solution; in the mixed solution, the molar ratio of SnCl4·5H2O, Sb2O3 and La(NO3)3·6H2O is in the range of 100:10:0.5 to 100:10:3, wherein Sn 4+ The concentration is 0.3-0.6 mol / L; the volume ratio of isopropanol, hydrochloric acid and citric acid is 100:2:125, wherein the concentration of hydrochloric acid is 35%-40%, and the concentration of citric acid is 10%-20%.
[0025] Preferably, in step S4, the specific current density range is 10 to 40 mA.cm-2, and the deposition time is 15 to 30 minutes.
[0026] Preferably, in step S4, the calcination temperature is greater than 500° C., and the calcination time ranges from 1 to 2 hours.
[0027] In the third aspect, the present invention also discloses a method for treating dye wastewater, using the DSA electrode as described above, placing the DSA electrode as an anode into the dye wastewater, taking a titanium substrate as a cathode and placing it into the same dye wastewater, connecting the anode and the cathode to the positive and negative electrodes of a power source respectively through electrical conductors; turning on the power source to degrade the organic dye components in the dye wastewater; the dye wastewater is dye wastewater containing rhodamine B, or dye wastewater containing methylene blue, or dye wastewater containing methyl orange.
[0028] The present invention has the following beneficial effects: the modification of the intermediate layer titanium dioxide nanotubes (TiO2-NTs) of the DSA electrode disclosed in the present invention can improve the electrocatalytic property and stability of the electrode without reducing the oxygen absorption potential, the ordered three-dimensional structure of TiO2-NTs effectively increases the load of the SnO2-Sb2O4-La coating and enhances the stability of the electrode, while the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs, and at the same time, the introduction of TiO2-NTs increases the load of the coating and improves the stability and pollutant degradation rate, thereby extending the service life of the electrode. The DSA electrode disclosed in the present invention can utilize the free radicals (such as hydroxyl free radicals, etc.) generated during the electrolysis process as oxidants to degrade pollutants when the electrochemical oxidation method is used to purify dye wastewater, and has the advantages of high efficiency and no secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to make the purpose, technical solution and advantages of the invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings, in which:
[0030] Figure 1 Schematic diagram of the DSA electrode structure of the present invention.
[0031] Figure 2 It is a schematic diagram of the dye wastewater treatment method of the present invention.
[0032] Figure 3 This is a SEM image of the Ti / TiO2-NTs electrode in Example 2 of the present invention.
[0033] Figure 4 This is the SEM image of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode in Example 2 of the present invention.
[0034] Figure 5 This is the SEM image of Ti / TiO2-NTs / SnO2-Sb2O4-La with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0035] Figure 6 This is a schematic diagram of the EDS results of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0036] Figure 7 This is a schematic diagram of the element mapping results of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0037] Figure 8 This is the XPS full spectrum of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0038] Fig. 9 This is a high-resolution scanning spectrum of Sn 3d of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0039] Fig.10 This is a high-resolution scanning spectrum of Sb 3d of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0040] Fig.11 This is a high-resolution scanning spectrum of La 3d of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0041] Fig.12This is a high-resolution scanning spectrum comparison of the Ti / SnO2-Sb2O4-La electrode in Example 2 of the present invention and the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode O1s with TiO2-NTs as the intermediate layer.
[0042] Fig.13 This is the XRD result of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0043] Fig.14 The different electrodes in Example 2 of the present invention are 0.3 mol.L -1 Sodium sulfate and 20mg.L-1 rhodamine B solution at 4mV.s -1 The cyclic voltammetry curves were scanned at a scan rate of .
[0044] Fig.15 The different electrodes in the second embodiment of the present invention are 10mV.s -1 Linear voltammetric curve of rate scan.
[0045] Fig.16 This is the effect of different electrodes on the degradation rate of RhB in Example 2 of the present invention.
[0046] Fig.17 This is a graph showing the change in absorption spectrum of the RhB solution treated with the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode using TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0047] Fig.18 It is a schematic diagram of the experimental results of quenching different free radicals in RhB solution treated with different electrodes in Example 2 of the present invention.
[0048] Fig.19 This is a schematic diagram of the results of treating different types of dye wastewater using the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0049] Fig. 20 This is a schematic diagram of the five-cycle degradation rate of Rhodamine B by Ti / TiO2-NTs / SnO2-Sb2O4-La with TiO2-NTs as the intermediate layer in Example 2 of the present invention.
[0050] Fig.21 It is a schematic diagram of accelerated life test of different electrodes in the second embodiment of the present invention.
[0051] Fig. 22 This is the effect of current density on the degradation rate of the dye component in Example 3 of the present invention.
[0052] Fig.23 This is the effect of electrolyte concentration on the degradation rate of the dye component in Example 3 of the present invention.
[0053] Fig.24 This is the effect of the solution pH value on the degradation rate of the dye component in Example 3 of the present invention.
[0054] Fig.25 This is the effect of the initial concentration on the degradation rate of the dye component in Example 3 of the present invention.
[0055] Explanation of the reference numerals: 1. DSA electrode; 11. Titanium substrate; 12. SnO2-Sb2O4-La composite material layer; 13. TiO2-NTs intermediate layer; 2. Electric conductor; 3. Cathode; 4. Dye wastewater; 5. Power supply. DETAILED DESCRIPTION
[0056] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0057] It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. In the description of the present invention, it should be noted that the orientation or position relationship indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or position relationship shown in the drawings, or the orientation or position relationship in which the invention product is usually placed when used, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance. In addition, the terms "horizontal", "vertical", etc. do not mean that the components are absolutely horizontal or suspended, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted. In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0058] The present invention can be applied to the technical field of purifying dye wastewater by electrocatalytic oxidation, and is particularly suitable for the field of purifying dye wastewater, and solves the technical problems in the prior art that traditional DSA electrodes have decreased activity and short service life when treating dye wastewater.
[0059] The DSA electrode disclosed in the present invention can have a good treatment effect on common dye components, including but not limited to rhodamine B (RhB), methylene blue (MB) and methyl orange (MO). Rhodamine B (RhB), methylene blue (MB) and methyl orange (MO) are used for research in the embodiments of the present invention, but it does not mean that the DSA electrode disclosed in the present invention can only be used to treat these three dye components. It has a good treatment effect on other common dye components.
[0060] First, see Figure 1 Based on the technical problems solved above, the present invention discloses a DSA electrode 1 for purifying dye wastewater 4, comprising a titanium substrate 11, on which a TiO2-NTs intermediate layer 13 is attached, and a SnO2-Sb2O4-La composite material layer 12 is attached to the side of the TiO2-NTs intermediate layer 13 away from the titanium substrate, wherein the thickness of the SnO2-Sb2O4-La composite material layer is 0.2 to 0.8 mm.
[0061] The morphological characteristics of the DSA electrode disclosed in the present invention are as follows: TiO2-NTs clusters are prepared by an anodic oxidation method and are closely arranged on the surface of a titanium sheet. The present invention refers to the above electrode as a Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as an intermediate layer, and the surface of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as an intermediate layer presents a coral stone-like structure.
[0062] The modification of the intermediate layer of the DSA electrode disclosed in the present invention with titanium dioxide nanotubes (TiO2-NTs) can improve the electrocatalytic performance and stability of the electrode without reducing the oxygen absorption potential. The ordered three-dimensional structure of TiO2-NTs effectively increases the load of the SnO2-Sb2O4-La coating and enhances the stability of the electrode. At the same time, the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs. At the same time, the introduction of TiO2-NTs increases the load of the coating and improves the stability and pollutant degradation rate, thereby extending the service life of the electrode.
[0063] The DSA electrode disclosed in the present invention can utilize free radicals (such as hydroxyl free radicals, etc.) generated during the electrolysis process as oxidants to degrade pollutants when using an electrochemical oxidation method to purify dye wastewater, and has the advantages of high efficiency and no secondary pollution.
[0064] Preferably, the dye wastewater is dye wastewater containing rhodamine B, or dye wastewater containing methylene blue, or dye wastewater containing methyl orange.
[0065] When this scheme was applied to the degradation of rhodamine B, the current density was 30 mA cm -2 When the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer can completely degrade Rhodamine B in 15 minutes. Under the same conditions, the degradation rates of other different dye wastewaters (methylene blue, methyl orange) can be completely degraded after 30 minutes. The concentration of the aforementioned dye components including Rhodamine B is 10-40 mg / L.
[0066] Specifically, the actual service life of the DSA electrode of this solution is higher than 3000 hrs.
[0067] Preferably, the titanium substrate is made of titanium sheet with a thickness of 0.5 to 2.0 mm.
[0068] The advantages of using titanium sheets are good stability and not easy to corrode after long-term use; high activity and can effectively promote oxidation reactions; low cost, simple manufacturing process, and economical materials; good mechanical properties, high strength, and resistance to harsh conditions; flexible processing and can be made into different shapes according to needs; corrosion resistance and resistance to erosion by a variety of chemical substances; high current efficiency, reduced energy consumption, and improved efficiency; low overpotential: reduced energy consumption; reusable, reducing replacement costs.
[0069] The use of the DSA electrode disclosed in the present invention has the following technical effects: the present invention uses Ti / TiO2-NTs / SnO2-Sb2O4-La electrode to degrade dye wastewater through electrochemical oxidation, and the ordered TiO2-NTs three-dimensional structure effectively increases the load of the SnO2-Sb2O4-La coating and enhances the stability of the electrode, thereby enhancing the electrocatalytic performance of the electrode. At the same time, the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs, while also reducing the risk of secondary pollution to the environment.
[0070] In a second aspect, the present invention further discloses a method for preparing a DSA electrode, using the DSA electrode as described above, comprising the following steps:
[0071] S1, pre-treating the titanium substrate;
[0072] S2, placing the pretreated titanium substrate into a reactor and using it as an anode to prepare a TiO2-NTs intermediate layer by an anodic oxidation method, wherein the TiO2-NTs intermediate layer is attached to the surface of the titanium substrate;
[0073] S3, using the titanium substrate with the TiO2-NTs intermediate layer attached thereto as a cathode, and depositing a SnO2-Sb2O4-La composite material deposition layer on the side of the TiO2-NTs intermediate layer away from the titanium substrate by an electrodeposition method;
[0074] S4. Calcine the titanium substrate with a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer, control the calcination temperature and time, and obtain a Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer, that is, the obtained DSA electrode.
[0075] This scheme prepares TiO2-NTs through a simple anodization method to form a very ordered three-dimensional structure of TiO2-NTs, which effectively increases the load of the SnO2-Sb2O4-La coating and enhances the stability of the electrode. At the same time, the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs.
[0076] This scheme adopts the method of first preparing an intermediate layer, then depositing, and then calcining to attach a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer on a titanium substrate. At the same time, during the deposition and calcination process, the ratio of each component, deposition time, calcination time and calcination temperature are controlled, so that the obtained DSA electrode can improve the electrocatalytic property and stability of the electrode without reducing the oxygen absorption potential when used to purify dye wastewater, and can have an efficient degradation rate and a high removal rate for the dye component.
[0077] In the specific implementation, in step S1, the titanium substrate is pretreated by first grinding it with sandpaper, then rinsing the ground titanium substrate with deionized water, then immersing it in a NaOH solution for degreasing, then immersing it in an oxalic acid solution for micro-boiling etching, and finally rinsing it with deionized water to obtain the pretreated titanium substrate.
[0078] Preferably, in step S2, preparing the TiO2-NTs intermediate layer includes the following steps: first, placing the pretreated titanium substrate in a mixed solution containing NH4F and ethylene glycol, using the titanium substrate as an anode and a graphite electrode as a cathode, oxidizing at a constant voltage to obtain amorphous TiO2-NTs, and then annealing at a constant temperature to obtain TiO2-NTs crystals, wherein the TiO2-NTs crystals are attached to the surface of the titanium substrate in a layered structure to obtain a titanium substrate with a TiO2-NTs intermediate layer attached.
[0079] Preferably, in step S3, depositing the SnO2-Sb2O4-La composite material layer comprises the following steps:
[0080] S3.1. Place a titanium substrate with a TiO2-NTs intermediate layer in a reactor and use it as a cathode. Use a graphite electrode as an anode. Connect the cathode and the anode to the negative and positive electrodes of a power source through electrical wires, respectively.
[0081] S3.2, preparing a mixed solution according to a preset mixing ratio, adjusting the pH of the mixed solution to acidic, and then adding the mixed solution to a reactor, wherein the raw materials used to prepare the mixed solution include SnCl4·5H2O, Sb2O3, and La(NO3)3·6H2O;
[0082] S3.3. Turn on the power supply to maintain a specific current density between the cathode and the anode, so that the substances in the mixed solution are deposited on the titanium substrate. After the preset deposition time, a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer is formed on the titanium substrate, and the deposition thickness is 0.2 to 0.8 mm.
[0083] Preferably, in step S2, the constant voltage is in the range of 20 to 30 V, the oxidation time is in the range of 150 to 200 min, the constant annealing temperature is above 400° C., and the annealing time is 1 to 2 h.
[0084] Preferably, in step S3, the mixed solution is prepared by sequentially adding SnCl4·5H2O, Sb2O3 and La(NO3)3·6H2O to an isopropanol solution, then sequentially adding hydrochloric acid and citric acid, and then first ultrasonicating and then stirring at a constant temperature to obtain a mixed solution; in the mixed solution, the molar ratio of SnCl4·5H2O, Sb2O3 and La(NO3)3·6H2O is in the range of 100:10:0.5 to 100:10:3, wherein Sn 4+ The concentration is 0.3-0.6 mol / L; the volume ratio of isopropanol, hydrochloric acid and citric acid is 100:2:125, wherein the concentration of hydrochloric acid is 35%-40%, and the concentration of citric acid is 10%-20%.
[0085] Preferably, in step S4, the specific current density range is 10-40 mA.cm -2 , the deposition time is 15 to 30 minutes.
[0086] Preferably, in step S4, the calcination temperature is greater than 500° C., and the calcination time ranges from 1 to 2 hours.
[0087] Preferably, the titanium substrate is made of titanium sheet with a thickness of 0.5 to 2.0 mm.
[0088] Specifically, in step S4, the titanium substrate to which the SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer is attached is placed in a tubular furnace at 600° C. and calcined for 120 minutes.
[0089] The preparation method of the DSA electrode disclosed in the present invention has the following technical effects: the preparation method of the DSA electrode adopts the method of first preparing an intermediate layer, then depositing, and then calcining, and attaching a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer on a titanium substrate. At the same time, during the deposition and calcination process, the ratio of each component, the deposition time, the calcination time and the calcination temperature are controlled, so that the obtained DSA electrode can improve the electrocatalytic property and stability of the electrode without reducing the oxygen absorption potential when used to purify dye wastewater, and can have a high efficiency degradation rate and Higher removal rate; the modification of the intermediate layer of titanium dioxide nanotubes (TiO2-NTs) of the prepared DSA electrode can improve the electrocatalytic property and stability of the electrode without reducing the oxygen absorption potential; the ordered three-dimensional structure of TiO2-NTs effectively increases the load of SnO2-Sb2O4-La coating and enhances the stability of the electrode, while the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs. At the same time, the introduction of TiO2-NTs increases the load of the coating and improves the stability and pollutant degradation rate, thereby extending the service life of the electrode.
[0090] Third, see Figure 2 The present invention also discloses a method for treating dye wastewater, using the DSA electrode 1 as described above, placing the DSA electrode as an anode into dye wastewater 4, taking a titanium substrate 11 as a cathode 3, placing it into the same dye wastewater, connecting the anode and cathode 3 to the positive and negative electrodes of a power source 5 through an electrical conductor 2, respectively; turning on the power source 5 to degrade the organic dye components in the dye wastewater; the dye wastewater is dye wastewater containing rhodamine B, or dye wastewater containing methylene blue, or dye wastewater containing methyl orange.
[0091] In summary, the DSA electrode and its preparation method and the dye wastewater treatment method disclosed in the present invention have the following technical effects:
[0092] 1. The morphological characteristics of the DSA electrode disclosed in the present invention are as follows: TiO2-NTs clusters are prepared by anodization and are closely arranged on the surface of a titanium sheet. The surface of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer presents a coral stone-like structure.
[0093] 2. The modification of the intermediate layer of the DSA electrode disclosed in the present invention with titanium dioxide nanotubes (TiO2-NTs) can improve the electrocatalytic performance and stability of the electrode without reducing the oxygen absorption potential. The ordered three-dimensional structure of TiO2-NTs effectively increases the load of the SnO2-Sb2O4-La coating and enhances the stability of the electrode. At the same time, the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs. At the same time, the introduction of TiO2-NTs increases the load of the coating and improves the stability and pollutant degradation rate, thereby extending the service life of the electrode.
[0094] 3. The DSA electrode disclosed in the present invention can utilize the free radicals (such as hydroxyl radicals, etc.) generated during the electrolysis process as oxidants to degrade pollutants when using the electrochemical oxidation method to purify dye wastewater, and has the advantages of high efficiency and no secondary pollution.
[0095] 4. The preparation method of the DSA electrode adopts the method of first preparing an intermediate layer, then depositing, and then calcining, and attaching a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer on a titanium substrate. At the same time, during the deposition and calcination process, the ratio of each component, the deposition time, the calcination time and the calcination temperature are controlled, so that when the obtained DSA electrode is used to purify dye wastewater, the electrocatalytic property and stability of the electrode can be improved without reducing the oxygen absorption potential, and the dye component can have a high degradation rate and a high removal rate; the prepared D The modification of the intermediate layer of SA electrode with titanium dioxide nanotubes (TiO2-NTs) can improve the electrocatalytic performance and stability of the electrode without reducing the oxygen absorption potential; the ordered three-dimensional structure of TiO2-NTs effectively increases the loading of SnO2-Sb2O4-La coating and enhances the stability of the electrode. At the same time, the SnO2-Sb2O4-La coating helps to alleviate the adverse effects of the high resistivity of TiO2-NTs. At the same time, the introduction of TiO2-NTs increases the loading of the coating and improves the stability and pollutant degradation rate, thereby extending the service life of the electrode.
[0096] 5. When the dye wastewater treatment method of the present invention is applied to the degradation of Rhodamine B, the current density is 30 mA cm -2 When the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer can completely degrade Rhodamine B in 15 minutes. Under the same conditions, the degradation rates of other different dye wastewaters (methylene blue, methyl orange) can be completely degraded after 30 minutes, which can be effectively used in the treatment of dye wastewater.
[0097] In order to further optimize or illustrate the DSA electrode and its preparation method, and the dye wastewater treatment method of the present invention, the present invention discloses the following embodiments.
[0098] Embodiment 1
[0099] In this embodiment, a 80 mm × 20 mm × 1 mm titanium sheet is used as a titanium substrate to prepare a DSA electrode having a Ti / TiO2-NTs / SnO2-Sb2O4-La composite material layer attached thereto with TiO2-NTs as an intermediate layer.
[0100] First, the titanium sheet was pretreated by sanding a 80 mm × 20 mm × 1 mm titanium sheet until the surface showed a silvery white metallic luster, then the polished titanium sheet was rinsed with deionized water, ultrasonically degreased with 6% NaOH for 150 minutes, slightly boiled and etched in 20% oxalic acid solution for 120 minutes, then rinsed with deionized water, and stored in methanol;
[0101] The TiO2-NTs intermediate layer was prepared by anodization. The pretreated Ti plate was placed in ethylene glycol containing 0.5wt% NH4F and 4Vol% H2O, and oxidized at a constant voltage of 25V for 180 minutes (titanium sheet as anode and graphite as cathode) to obtain amorphous TiO2-NTs, which were annealed at 500°C for 120 minutes to obtain crystalline TiO2-NTs.
[0102] SnO2-Sb2O4-La was prepared by electrodeposition. SnCl4.5H2O, Sb2O3 and La(NO3)3·6H2O were added to 40 mL of isopropanol solution, and the molar ratio of each component was 100:10:1. 4+ The concentration is 0.5mol / L, and then 0.8mL hydrochloric acid (37%) and 5mL citric acid (10%) are added, and the solution is placed in an ultrasonic machine at a constant temperature of 25°C for 20 minutes, and then magnetically stirred for 60 minutes, and finally deposited at a constant current of 0.12A for 25 minutes, and the effective area is 30mm×20mm×1mm. The anode uses a graphite electrode, and the deposited titanium sheet is placed in a tubular furnace at 550°C and calcined for 150 minutes.
[0103] The DSA electrode of this embodiment is prepared by anodization method. TiO2-NTs clusters are closely arranged on the surface of the titanium sheet. The surface of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer presents a coral stone structure, which is mainly attributed to the presence of the TiO2-NTs intermediate layer. This three-dimensional structure is conducive to increasing the contact area, generating more active sites, and improving the electrocatalytic ability.
[0104] The DSA electrode of this example was tested for its electrocatalytic performance in 100 mL of simulated dye wastewater containing 0.1 mol / L Na2SO4 and 20 mg / L Rhodamine B (RhB). The prepared electrode was used as the anode and the titanium sheet as the cathode at a current density of 30 mA / cm 2 The solution was sampled every 5 minutes, and the absorbance of RhB at a specific wavelength of 554 nm was measured by UV-Vis spectrophotometer (UV6100), and the decolorization rate of RhB was calculated based on the absorbance.
[0105] The accelerated life of the electrode was investigated by using Ti / TiO2-NTs / SnO2-Sb2O4-La (effective area of 20 mm × 20 mm) as the anode and titanium sheet as the cathode in 1 M H2SO4 at 1000 mA / cm 2 When the cell voltage reached 10 V, the electrode was considered inactivated and the duration of the test was recorded as the accelerated life of the electrode.
[0106] Study on the free radical cleaning of ·OH and SO4 using tert-propanol (TBA) and methanol (CH3OH) -2 Effect on RhB degradation.
[0107] The physical and chemical properties and electrochemical performance of the DSA electrode prepared in this embodiment were analyzed by SEM, XRD, XPS and electrochemical tests (CV, LSV). The results showed that TiO2-NTs were densely accumulated on the surface of the Ti substrate, which improved the binding force of the SnO2-Sb2O4-La coating and provided a larger specific surface area and more active sites for the degradation of RhB. When the solution pH was 3.0, the electrolyte concentration was 0.1M, and the current density was 30mA / cm 2 The decolorization rate of RhB reached 100% after 15 minutes when treating 20 mg / L RhB solution. In addition, the accelerated life of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer reached 200 minutes (1000 mA / cm 2 ,1M H2SO4), the actual service life is up to 3699 hours. Finally, based on the free radical quenching experiment, it is proved that OH plays a major role in the degradation process. Adding TiO2-NTs intermediate layer not only improves the degradation efficiency, but also solves the problem of short service life of DSA electrode, which provides a basis for the large-scale application of DSA electrode.
[0108] Embodiment 2
[0109] In this embodiment, a titanium sheet is used as a titanium substrate to prepare a DSA electrode having a Ti / TiO2-NTs / SnO2-Sb2O4-La composite material layer with TiO2-NTs as an intermediate layer. The specification of the titanium substrate is 70 mm×20 mm×2 mm.
[0110] First, the titanium plate was polished with sandpaper until the surface showed a silvery white metallic luster, then rinsed with deionized water, degreased with 5% NaOH for 2 hours, slightly etched in 15% oxalic acid solution for 2 hours, rinsed with deionized water, and stored in methanol.
[0111] The TiO2-NTs intermediate layer was prepared by anodization. The pretreated Ti plate was placed in ethylene glycol containing 0.5wt% NH4F and 4Vol% H2O and oxidized at a constant voltage of 30V for 3h (titanium plate as anode and graphite as cathode) to obtain amorphous TiO2-NTs, which were annealed at 500℃ for 120min to obtain crystalline TiO2-NTs.
[0112] SnO2-Sb2O4-La was prepared by electrodeposition. SnCl4.5H2O, Sb2O3 and LaN3O9·6H2O were added to 40 ml of isopropanol solution, and the molar ratio of each component was 100:10:1. 4+ The concentration is 0.5 mol L -1 , then add 0.8ml hydrochloric acid (37%) and 5ml citric acid (10%), place the solution in an ultrasonic machine at a constant temperature of 25℃ for 15min, then stir it magnetically for 1h, and finally deposit it at a constant current of 0.12A for 15min, with an effective area of 30mm×20mm×1mm. The anode uses a graphite electrode, and the deposited titanium plate is placed in a tubular furnace at 550℃ and calcined for 2h.
[0113] 1. Qualitative and semi-quantitative analysis of electrode surface morphology and elements
[0114] The electrode surface morphology analysis was carried out on a field emission electron scanning microscope (SEM), and the qualitative and semi-quantitative composition of the elements was analyzed by an energy dispersive detector (EDS). The crystal structure of the produced material was evaluated by X-ray diffractometer (XRD), and the elemental composition and valence state of the electrode surface were measured and analyzed by X-ray photoelectron spectrometer (XPS). Electrochemical tests were carried out using a conventional three-electrode cell system (working electrode: Ti / TiO2-NTs / SnO2-Sb2O4-La, reference electrode: saturated calomel electrode (SCE), auxiliary electrode: Pt electrode), and electrochemical analysis was performed using a CHI600E electrochemical workstation. At 20 mg.L -1 Rhodamine B and 0.1 mol.L -1Cyclic linear voltammetry (CV) of the test electrode in Na2SO4 with a scan range of -0.5-2.0 V. The oxygen evolution potential (OEP) of the electrode was measured by linear sweep voltammetry (LSV) with a scan range of 0.5-2.5 V. 5 Hz-0.1Hz, amplitude 10mV.s -1 Electrochemical impedance spectroscopy (EIS) was measured under the following conditions.
[0115] Figure 3 This is the SEM image of titanium dioxide nanotubes prepared by anodization. From the image, it can be seen that TiO2-NTs clusters are densely accumulated on the surface of the titanium plate. Through the SEM images of Ti / SnO2-Sb2O4-La and Ti / TiO2-NTs / SnO2-Sb2O4-La ( Figure 4 and Figure 5 ) It can be found that the surface of the Ti / SnO2-Sb2O4-La electrode is in the form of fine particles, while the surface of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer presents a corallite-like structure, which is mainly attributed to the presence of the TiO2-NTs intermediate layer. This three-dimensional structure is conducive to increasing the contact area, generating more active sites, and improving the electrocatalytic ability.
[0116] Figure 6 The EDS results of the electrode show that the electrode surface is composed of four elements: O, Sn, Sb and La, indicating that La is successfully doped into the electrode and that Sn, Sb and La generate corresponding oxides. Figure 7 The element mapping in the graph shows the uniform distribution of the four elements O, Sn, Sb and La in the coating, proving that the active coating is evenly covered on the TiO2-NTs intermediate layer. It is also due to the existence of the TiO2-NTs intermediate layer that a dense SnO2-Sb2O4-La coating is formed on the electrode surface, which is beneficial to prolong the service life of the electrode.
[0117] XPS test shows that it is helpful to further analyze the existence form of elements in the electrode. Figure 8 It can be seen from the full spectrum that the electrode is mainly composed of Sn, Sb, La and O elements, and the presence of C element is mainly attributed to the organic carbon contamination on the electrode surface. Fig. 9 There are two asymmetric peaks in Sn 3d 3 / 2 and Sn 3d 5 / 2 , corresponding to the binding energy positions of 495.75eV and 487.36eV, respectively, indicating that Sn exists in the +4 valence state and in the form of SnO2. Fig.10 It can be seen that there is Sb 3d 3 / 2 and Sb3d 5 / 2The two asymmetric peaks, corresponding to the binding energy positions of 540.41 eV and 531.24 eV, indicate that Sb exists in the form of Sb2O4 (Sb2O3·Sb2O5). Fig.11 The binding energy positions of La 3d are 855.58eV, 852.25eV, 838.50eV and 836.50eV, respectively, indicating that La may exist in the form of La2O3 or La(OH)3. The binding energy position of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer is slightly higher than that of the Ti / SnO2-Sb2O4-La electrode ( Fig.12 ), which may be due to the fact that the addition of TiO2-NTs makes the chemical bonds between oxygen atoms and other elements more stable. At the same time, compared with the Ti / SnO2-Sb2O4-La electrode, the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has an increased content of hydroxyl oxygen species (Oads) by 0.41%, and the corresponding lattice oxygen species (Olat) content has increased by 2.39%. This indicates that the TiO2-NTs / SnO2-Sb-La electrode has better OH generation ability, thereby improving the electrocatalytic performance and improving the degradation efficiency.
[0118] 2. Crystal structure analysis
[0119] XRD patterns are used to identify the crystal phases of different electrodes ( Fig.13 ). The XRD pattern of Ti / TiO2-NTs shows that there is obvious α-TiO2 at 25.3°, the corresponding crystal plane is 101, which is anatase phase, and its catalytic performance is better than that of rutile phase.
[0120] Ti / SnO2-Sb2O4-La, Ti / TiO2-NTs / SnO2-Sb2O4-La electrodes with TiO2-NTs as intermediate layer at 2Theta=
[0121] The diffraction peaks at 26.61, 33.89 and 51.78 correspond to the (110),
[0122] The diffraction peak width of Ti / SnO2-Sb2O4-La is narrower than that of Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer, indicating that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has finer grains. At the same time, no TiO2 was detected, indicating that the SnO2-Sb2O4-La coating has good coating properties. Sb and La elements were not detected, which may be because their concentrations are less than the instrument detection limit or they enter the SnO2 lattice in a substitution manner without forming an ordered lattice structure.
[0123] 4. Electrochemical test
[0124] Fig.14 The CV curves of different electrodes are shown in Figure 1. As can be seen from the figure, the electrode with TiO2-NTs as the substrate has a larger area, indicating that the electrode has more catalytic active sites. At the same time, the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has a lower oxygen potential than other electrodes, which helps to improve the electrocatalytic performance of the electrode in treating wastewater. The LSV curves of different electrodes are shown in Figure 1. Fig.15 As shown. It can be seen from the figure that at low potential, the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has a stronger current response. At the same time, compared with the Ti / SnO2 (2.31V), Ti / SnO2-Sb2O4 (2.14V), and Ti / SnO2-Sb2O4-La (1.98V) electrodes, the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has a lower RhB decomposition potential (1.82), indicating that the electrode has a higher current efficiency, improves the electrocatalytic degradation efficiency of organic pollutants, and reduces the energy consumption of side reactions when treating the same amount of pollutants. At the same time, this shows that the electrode has a higher current efficiency, inhibits the generation of oxygen, improves the electrocatalytic degradation efficiency of organic pollutants, and reduces the energy consumption of side reactions when treating the same amount of pollutants.
[0125] Next, the catalytic performance of the electrode with the SnO2-Sb2O4-La composite material layer attached with TiO2-NTs as the intermediate layer obtained in this example is analyzed:
[0126] In 100 mL, 0.1 mol L -1 Na2SO4, 20mg L -1 The electrocatalytic performance of the electrode was tested in the simulated dye wastewater of RhB. The prepared electrode was used as the anode and the titanium plate as the cathode at a current density of 30 mA cm-2 RhB was degraded at a constant current for 30 mins under the condition of . The absorbance of RhB at a specific wavelength of 554 nm was measured by UV-Vis spectrophotometer (UV6100), and the degradation rate of RhB was calculated by substituting it into formula 1. The accelerated life of the electrode was calculated by using Ti / TiO2-NTs / SnO2-Sb2O4-La (effective area of 20 mm × 20 mm) as the anode and titanium plate as the cathode in 1M H2SO4 at 1 mA cm -2 The electrode was considered inactivated when the cell voltage reached 10V, and the duration of the test was recorded as the accelerated life of the electrode. -2 Finally, the possible degradation pathways of RhB were detected by gas chromatography-mass spectrometry (GC-MS). After the sample was extracted with dichloromethane, 3 μL of the sample was injected in splitless mode at an injection port temperature of 250 °C, and then the column temperature was maintained at 40 °C for 5 min and 4 °C min -1 The temperature was raised to 300 °C and maintained at 300 °C for 5 min. The carrier gas (He) rate was 1 mL min -1 , the ion source temperature is maintained at 230 ~ 250 ° C.
[0127] 5. Degradation performance and stability test of electrode
[0128] (1) Degradation efficiency of RhB by different electrodes
[0129] Fig.16 When the current density is 30 mA cm -1 , when the solution pH is 3.0, 20 mg L containing 0.1 M Na2SO4 -1 The degradation rate and kinetic fitting of RhB solution under different electrodes. It can be seen from the figure that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer reaches 100% after 15 minutes of degradation, and the Ti / SnO2, Ti / SnO2-Sb2O4, and Ti / SnO2-Sb2O4-La electrodes reach 75.11%, 82.72%, and 99.84% after 30 minutes of degradation, respectively. Among them, the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer shows excellent electrocatalytic degradation efficiency. Kinetic fitting of the degradation process of Rhodamine B shows that the relationship between the degradation rate of Rhodamine B and time conforms to the pseudo-first-order kinetic equation. The results show that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer reaches the fastest reaction kinetic constant k (0.2298min -1), respectively Ti / SnO2(0.0463min -1 )、Ti / SnO2-Sb2O4(0.0592min -1 ), Ti / SnO2-Sb2O4-La(0.1952min -1 This may be because the addition of TiO2-NTs as an intermediate layer provides a channel for electron transmission, the electrochemical activity of the SnO2-Sb2O4-La coating increases, and the conductivity of the electrode is improved, so that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer exhibits excellent electrocatalytic degradation efficiency.
[0130] (2) UV-vis
[0131] UV-vis spectra of electrocatalytic degradation at different times are shown in Figure 2. Fig.17 As shown. It can be found that there is an obvious absorption peak at an absorption wavelength of 554nm. The absorption peak here is mainly due to the influence of the RhB chromosphere structure. As time goes by, the absorption peak value decreases, indicating that the conjugated structure of RhB is destroyed. From the figure, it can be seen that the absorption peak of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer disappears after 15 minutes of electrocatalytic degradation, indicating that the electrode can quickly destroy the conjugated structure of RhB during the degradation process and shows excellent decolorization efficiency without the emergence of new functional groups.
[0132] In order to further study the degradation effect of Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer on RhB, the effect of different electrodes on TOC removal efficiency was also discussed ( Fig.18 ). As can be seen from the figure, the TOC removal rate of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer reached 86.13% after 30 minutes, which is higher than Ti / SnO2 (51.92%), Ti / SnO2-Sb2O4 (64.32%), and Ti / SnO2-Sb2O4-La (80.41%), indicating that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer can effectively degrade RhB. It can be found that the TOC removal rate of RhB is lower than its degradation rate, which may be due to the partial degradation of RhB into small molecular organic matter.
[0133] (3) Degradation of different dye wastewaters
[0134] Fig.19It shows the degradation efficiency of the electrode when treating different dye wastewaters. As can be seen from the figure, for different dye wastewaters, rhodamine B (RhB), methylene blue (MB) and methyl orange (MO) all reach 100% after 30 minutes of degradation. This shows that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has a good treatment effect when treating different dye wastewaters, has a wide range of applications, and can provide practical application value for wastewater treatment.
[0135] (4) Cycle test
[0136] The reusability of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the interlayer was evaluated by five cycles of RhB removal experiments. Fig. 20 ). As shown in the figure, after 5 consecutive decolorization experiments, the degradation rate can still reach 93.28% after 30mins, which only decreased by 6.72%, indicating that the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has good reusability and can stably remove organic pollutants, which is conducive to its potential large-scale industrial application.
[0137] (5) Accelerated life test
[0138] In 1.0M H2SO4 electrolyte and 500mA.cm -2 Accelerated life tests were performed on different electrodes under high current density conditions to verify the working life of different electrodes. Fig.21 As shown in the figure, the accelerated life of the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer is 200 min, which is 14, 6, and 2 times that of the Ti / SnO2, Ti / SnO2-Sb2O4, and Ti / SnO2-Sb2O4-La electrodes, respectively. In order to make the comparison results more intuitive, the actual service life of Ti / TiO2-NTs / SnO2-Sb2O4-La is calculated to be 3699 hrs according to the Correa-Lozano formula, which is higher than that of Ti / SnO2 (185 hrs), Ti / SnO2-Sb2O4 (556 hrs), and Ti / SnO2-Sb2O4-La (1667 hrs) electrodes. The significant increase in service life may be attributed to the addition of the TiO2-NTs intermediate layer as an excellent carrier, which improves the stability of the electrode. In addition, one of the most likely mechanisms for the final deactivation of the electrode is due to the interaction between the Ti substrate and O2 in the wastewater. - The ionic reaction produces an insulating TiO2 layer.
[0139] Embodiment 3
[0140] Based on the conclusion of Example 2, the DSA electrode Ti / TiO2-NTs / SnO2-Sb2O4-La was prepared using SnCl4.5H2O, Sb2O3 and LaN3O9·6H2O with a molar ratio of 100:10:1, and the effects of different current density, electrolyte concentration, solution pH value, and initial concentration on the final treatment effect of the DSA electrode were investigated.
[0141] 1. Current density
[0142] The effect of current density on electrocatalytic performance Fig. 22 As shown in Figure 2, increasing the current density can achieve a high yield of free radicals, thereby increasing the degradation rate of RhB. -1 Up to 40mAcm -1 , the time for the degradation rate of RhB to reach 100% was advanced from 30mins to 15mins.
[0143] 2. Electrolyte concentration
[0144] Adding an appropriate amount of electrolyte Na2SO4 to the treated dye wastewater can reduce the resistance of the solution, thereby increasing the electron transfer between the two electrodes, reducing energy consumption, and improving the degradation rate of pollutants. The effect of different concentrations of electrolyte on the degradation efficiency is as follows: Fig.23 As shown. When the concentration of Na2SO4 increases from 0.1 mol L -1 Increase to 0.5 mol L -1 The degradation efficiency of RhB gradually increases. The appropriate amount of Na2SO4 accelerates the electron transfer efficiency, and more electrons are absorbed to produce an appropriate amount of S2O8 - , showing high oxidation activity and longer life, which contributes to the formation of H2O2 and ·OH and promotes the degradation of RhB; excessive Na2SO4 is not conducive to the degradation of organic pollutants because excessive SO4 2- Adsorbed on the anode surface, reducing the active sites on the anode surface, while excess SO4 2- It can also scavenge the transferred electrons and directly compete with the consumed electrons for ·OH, resulting in a decrease in ·OH.
[0145] 3. Solution pH
[0146] Fig.24It shows the effect of different pH values on the degradation rate of RhB. As can be seen from the figure, the degradation rate is best at pH = 3.0, reaching 100% in only 15 minutes. The degradation rate decreases under other acidic (pH = 2.0, 4.0, 5.0), neutral (pH = 7.0) and alkaline (pH = 9.0, 11.0) conditions. Because acidic conditions are conducive to the formation of H2O2, as the concentration of H2O2 increases, the concentration of ·OH produced also increases accordingly. However, in over-acidic conditions, the excessive acid solution increases the corrosiveness of the electrode, thereby reducing the catalytic activity of the electrode, shortening the service life of the electrode, and causing the degradation rate to decrease. Under alkaline conditions, oxygen evolution reaction is more likely to occur on the electrode surface, which causes the degradation rate of RhB to decrease. During the solution treatment process, it was also found that the pH value increased (pH = 5.0). This is mainly because the electrochemical degradation process will produce highly oxidizing ·OH, which consumes H + , causing the pH to increase.
[0147] 4. Initial concentration
[0148] In actual dye wastewater treatment, the fluctuation of the initial concentration of the solution will affect the degradation efficiency. Therefore, this example takes Rhodamine B as an example to explore the effect of different initial concentrations of RhB on the degradation rate ( Fig.25 ). At an initial concentration of 10 mg L -1 and 20 mg L -1 The degradation rates reached 100% in 15mins and 20mins, respectively, and 30mg L -1 and 40 mg L -1 The degradation rates of RhB solution in 30 minutes were 98.57% and 95.91%, respectively. Under certain conditions, the ·OH produced in the degradation process is limited. As the initial concentration of the solution increases, the ·OH required to be consumed also increases, resulting in a large amount of pollutants being adsorbed on the electrode surface to inhibit mass transfer, resulting in a longer degradation time and a decreased degradation rate.
[0149] In summary, the electrodeposition process used in the above embodiments prepared La-doped Ti / TiO2-NTs / SnO2-Sb2O4-La electrodes with TiO2-NTs as the intermediate layer. The results of electrode characterization (SEM, XRD, XPS) and electrochemical testing (CV, LSV) showed that the TiO2-NTs intermediate layer was successfully prepared, and its three-dimensional structure increased the specific surface area, improved the coating adhesion, made the surface coating denser, and enhanced the conductivity of the electrode. At the same time, it has a higher oxygen evolution potential than Ti / SnO2, Ti / SnO2-Sb2O4 and Ti / SnO2-Sb2O4-La electrodes and a better degradation effect on rhodamine B. When the solution pH = 3.0, the electrolyte concentration is 0.1M, and the current density is 30mAcm -2 20mg L-1 The degradation rate and TOC removal rate of RhB in RhB solution reached 100% and 86.13% after 15min and 30min respectively. Under the same conditions, the degradation rate of different dye wastewaters could be completely degraded after 30mins. After 5 cycles, the degradation rate of RhB by Ti / TiO2-NTs / SnO2-Sb2O4-La was only reduced by 6.72%, and the accelerated life was twice that of the Ti / SnO2-Sb2O4-La electrode. The free radical quenching experiment found that the degradation of RhB was attributed to the direct oxidation of and the indirect oxidation of free radicals. The GC-MS analysis results showed that the conjugated chromophore structure of the RhB molecule was destroyed by active free radicals in the initial stage. Then, an intermediate containing a benzene ring was generated, which was then gradually oxidized to form small organic compounds and finally mineralized into CO2 and H2O. In conclusion, the Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer has the advantages of simple preparation process, good electrocatalytic performance and good stability, and has broad application prospects in dye wastewater treatment.
[0150] In addition, this embodiment also adopts the same operation steps, taking rhodamine B as an example, at the initial concentration of rhodamine B
[0151] =30mg / L, solution pH=3, current density 30mA·cm -2 , electrolyte concentration 0.5 mol·L -1 Under the premise of , the deposition time was studied. The deposition time range is 15 to 30 min, and the deposition time is 10 min, 15 min, 20 min, 25 min, and 30 min respectively. As the deposition time increases and the coating thickens, the RhB degradation rate is improved, and the corresponding degradation rates are 80%, 81%, 98%, 97%, and 96%. For this embodiment, the decolorization rate reaches the best when the deposition time reaches 15 min, but when the deposition time continues to increase, the coating falls off due to being too thick and unstable, which leads to a decrease in the RhB degradation rate.
[0152] In addition, at the initial concentration of rhodamine B = 30 mg / L, solution pH = 3, and current density 30 mA cm -2 , electrolyte concentration 0.5 mol·L -1 As well as the premise of a deposition time of 15 min, other groups of experiments were carried out, as shown in Table 1.
[0153] Table 1 Degradation rate of Rhodamine B by electrocatalytic electrodes prepared under other parameter conditions
[0154]
[0155] It can be seen from the content of Table 2 that within the range of the influencing factor parameters disclosed in the present invention, the electrocatalytic electrode and the preparation method thereof disclosed in the present invention have a good degradation rate (greater than 98%) for the degradation of Rhodamine B, and can effectively remove the dye component of Rhodamine B in the dye wastewater.
[0156] It is understood that the present invention is described by some embodiments, and those skilled in the art are aware that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. Under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. The embodiments described in the present invention are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention generally described and shown in the drawings herein may be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all other embodiments obtained by ordinary technicians in the art without creative work based on the embodiments in the present invention belong to the scope of protection of the present invention.
Claims
1. A DSA electrode for purifying dye wastewater, characterized in that: It comprises a titanium substrate, on which a TiO2-NTs intermediate layer is attached, and a SnO2-Sb2O4-La composite material layer is attached to the side of the TiO2-NTs intermediate layer away from the titanium substrate, wherein the SnO2-Sb2O4-La composite material layer has a thickness of 0.2-0.8 mm.
2. The DSA electrode according to claim 1, characterized in that The dye wastewater is dye wastewater containing rhodamine B, or dye wastewater containing methylene blue, or dye wastewater containing methyl orange.
3. A method for preparing a DSA electrode, using the DSA electrode as claimed in claim 1, characterized in that: The following steps are involved: S1, pre-treating the titanium substrate; S2, placing the pretreated titanium substrate into a reactor and using it as an anode to prepare a TiO2-NTs intermediate layer by an anodic oxidation method, wherein the TiO2-NTs intermediate layer is attached to the surface of the titanium substrate; S3, using the titanium substrate with the TiO2-NTs intermediate layer attached thereto as a cathode, and depositing a SnO2-Sb2O4-La composite material deposition layer on the side of the TiO2-NTs intermediate layer away from the titanium substrate by an electrodeposition method; S4. Calcine the titanium substrate with a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer, control the calcination temperature and time, and obtain a Ti / TiO2-NTs / SnO2-Sb2O4-La electrode with TiO2-NTs as the intermediate layer, that is, the obtained DSA electrode.
4. The method for preparing a DSA electrode according to claim 3, characterized in that: In step S2, the preparation of the TiO2-NTs intermediate layer includes the following steps: first, the pretreated titanium substrate is placed in a mixed solution containing NH4F and ethylene glycol, the titanium substrate is used as an anode, and a graphite electrode is used as a cathode, and oxidation is performed at a constant voltage to obtain amorphous TiO2-NTs, and then annealing is performed at a constant temperature to obtain TiO2-NTs crystals, and the TiO2-NTs crystals are attached to the surface of the titanium substrate in the form of a layered structure to obtain a titanium substrate with a TiO2-NTs intermediate layer attached.
5. The method for preparing a DSA electrode according to claim 3, characterized in that: In step S3, depositing the SnO2-Sb2O4-La composite material layer comprises the following steps: S3.
1. Place a titanium substrate with a TiO2-NTs intermediate layer in a reactor and use it as a cathode. Use a graphite electrode as an anode. Connect the cathode and the anode to the negative and positive electrodes of a power source through electrical wires, respectively. S3.2, preparing a mixed solution according to a preset mixing ratio, adjusting the pH of the mixed solution to acidic, and then adding the mixed solution to a reactor, wherein the raw materials used to prepare the mixed solution include SnCl4·5H2O, Sb2O3, and La(NO3)3·6H2O; S3.
3. Turn on the power supply to maintain a specific current density between the cathode and the anode, so that the substances in the mixed solution are deposited on the titanium substrate. After the preset deposition time, a SnO2-Sb2O4-La composite material deposition layer with TiO2-NTs as the intermediate layer is formed on the titanium substrate, and the deposition thickness is 0.2 to 0.8 mm.
6. The method for preparing a DSA electrode according to claim 4, characterized in that: In step S2, the constant voltage is in the range of 20 to 30 V, the oxidation time is in the range of 150 to 200 min, the constant annealing temperature is above 400° C., and the annealing time is 1 to 2 h.
7. The method for preparing a DSA electrode according to claim 5, characterized in that: In step S3.2, the mixed solution is prepared by sequentially adding SnCl4·5H2O, Sb2O3 and La(NO3)3·6H2O to an isopropanol solution, and then sequentially adding hydrochloric acid and citric acid, and then first ultrasonicating and then stirring at a constant temperature to obtain a mixed solution; in the mixed solution, the molar ratio of SnCl4·5H2O, Sb2O3 and La(NO3)3·6H2O is in the range of 100:10:0.5 to 100:10:3, wherein Sn 4+ The concentration is 0.3-0.6 mol / L; the volume ratio of isopropanol, hydrochloric acid and citric acid is 100:2:125, wherein the concentration of hydrochloric acid is 35%-40%, and the concentration of citric acid is 10%-20%.
8. The method for preparing a DSA electrode according to claim 5, characterized in that: In step S3.3, the specific current density range is 10 to 40 mA cm -2 , the deposition time is 15 to 30 minutes.
9. The method for preparing a DSA electrode according to claim 5, characterized in that: In step S4, the calcination temperature is greater than 500° C., and the calcination time ranges from 1 to 2 hours.
10. A method for preparing a DSA electrode, using the DSA electrode as claimed in claim 2, characterized in that: A DSA electrode is placed as an anode in dye wastewater, and a titanium substrate is placed as a cathode in the same dye wastewater. The anode and the cathode are connected to the positive and negative electrodes of a power source through electrical conductors, respectively. The power source is powered on to degrade the organic dye components in the dye wastewater.
